Biomaterial-based possibilities for managing peri-implantitis - de Avila, Erica D. [UNESP] (2020)
Peri-implantitis is an inflammatory disease of hard and soft tissues around osseointegrated implants, followed by a progressive damage of alveolar bone. Oral microorganisms can adhere to all types of surfaces by the production of multiple adhesive factors. Inherent properties of materials will influence not only the number of microorganisms, but also their profile and adhesion force onto the material surface. In this perspective, strategies to reduce the adhesion of pathogenic microorganisms on dental implants and their components should be investigated in modern rehabilitation concepts in implant dentistry. To date, several metallic nanoparticle films have been developed to reduce the growth of pathogenic bacteria. However, the main drawback in these approaches is the potential toxicity and accumulative effect of the metals over time. In view of biological issues and in attempt to prevent and/or treat peri-implantitis, biomaterials as carriers of antimicrobial substances have attracted special attention for application as coatings on dental implant devices. This review will focus on biomaterial-based possibilities to prevent and/or treat peri-implantitis by describing concepts and dental implant components suitable for engagement in preventing and treating this disease. Additionally, we raise important criteria referring to the geometric parameters of dental implants and their components, which can directly affect peri-implant tissue conditions. Finally, we overview currently available biomaterial systems that can be used in the field of oral implantology.